The ethics of a clinical trial when the protocol clashes with international guidelines - Lan, N. T. N. (Public Health Action, 2013)
Due to their nature and complexity, clinical trials often take some time to launch after the protocol has been designed and ethics approval obtained. During this time, there may be changes in international treatment guidelines and recommendations that result in a conflict between study protocol and recommended international best practice. Here, we describe the situation that arose in a pharmacokinetic study on the use of two different doses of rifabutin in patients with human immunodeficiency virus-associated tuberculosis who initiated antiretroviral therapy (ART) with a lopinavir-ritonavir-based regimen in South Africa and Viet Nam. The study protocol specified that ART should be started 10 weeks after the start of anti-tuberculosis treatment. The study in South Africa was approved in June 2008, went ahead as scheduled and was completed in August 2010. The study in Viet Nam was approved in October 2008 and was started in June 2010. A few weeks later, the World Health Organization released their 2010 guidelines for adult ART; one of its strong recommendations (with moderate quality of evidence) was that ART should be started 2–8 weeks after the start of anti-tuberculosis treatment. Emerging scientific evidence also supported this recommendation. The investigators felt that the Viet Nam study protocol was in conflict with recommended international best practice, and the trial was stopped in October 2010. An amended study protocol in which ART was started at 2 weeks was developed and implemented. The ethics issues around this decision and the need to change the study protocol are discussed in this article.